Beyond Just the Average Effect: Variation in Head Start Treatment Effects on Parenting Behavior - Christina M. Padilla (SAGE Publishing, 2020)
Parent engagement has been a cornerstone of Head Start since its inception in 1965. Prior studies have found evidence for small to moderate impacts of Head Start on parenting behaviors but have not considered the possibility that individual Head Start programs might vary meaningfully in their effectiveness at improving parenting outcomes. The present study uses the Head Start Impact Study to examine the average effect of random assignment to and participation in Head Start on parenting outcomes as well as variation in that effect across Head Start programs. Findings reveal that Head Start is effective on average at promoting parents' daily reading and overall literacy and math activities with children but that effects vary significantly for parents' literacy and math activities, with some programs much more and some much less effective than their local alternatives. Findings also demonstrate that Head Start has consistent near-zero impacts across centers on parents' disciplinary interactions with children.